Application of the Kolb Experimental Learning Method to Marketing Management Material for Generation Z Students in the Economics Education Study Program, Al-Washliyah Muslim Nusantara University - Nasution, Isnan Nisa (Westscience Press, 2025)
Learning for Generation Z (Gen-Z) students in college today will not be optimal if it is only in mastering theory, but also in developing practical skills that are applicable, where Generation Z students who are thick with their characteristics of mastering IT will certainly only be enthusiastic in learning that involves IT and Social Media. Today's Gen-Z students are those who when they graduate will face social life and work that are certainly more challenging, so students need to be equipped with various IT skills that can support their lives and careers after graduating from college. One solution to the problem in developing practical skills for Gen-Z students in the context of the Marketing Management course, Gen-Z students are required to understand not only theoretical marketing concepts, but also be able to apply marketing concepts using various IT platforms and social media to be applied in designing, preparing and marketing various products and displaying them in real activities. One solution to the problem of developing skills is exploring students' experiences in applying Kolb's experimental learning method to marketing material in the Marketing Management course. This method consists of four stages of the learning cycle: concrete experience, reflective observation, abstract conceptualization, and active experimentation. This study used a qualitative approach with data collection techniques in the form of reflective interviews with 2A semester students of the Economics Education Study Program at Al-Washliyah Muslim Nusantara University. The results of the study showed that students experienced an active, contextual, and meaningful learning process. They marketed products such as fruit salad, balado spring rolls, donuts, spring rolls, and firecracker meatballs using direct marketing strategies and social media. Students identified challenges such as time constraints, market competition, and product technical constraints, but they overcame these through teamwork, time management, and quality improvement. This experience fostered self-confidence, creativity, and an interest in entrepreneurship. Students stated that this learning experience was more effective and beneficial than conventional theoretical learning.